MYANMAR CONFLICT RESOLUTION IN ASEAN PERSPECTIVE - Saragih, Hendra Maujana; Rianto, Dimas Aldi (Universitas Nasional, 2021)
ASEAN hopes to resolve Myanmar's current internal conflict because the military tends to be open to outsiders. Therefore, this paper tries to examine the state of military domination in Myanmar and how effective the attitude of ASEAN intervention is to its internal conflicts. s current internal conflict because the military tends to be open to outsiders. this study used a qualitative method. The method can be used to understand and explain how Myanmar's conflict resolution is from an ASEAN perspective. The result showed that Signs of democratic life in this country are sinking further with the strong will of the military to maintain and strengthen its power in the country. Therefore, it takes a big role from the international community to give spirit to every democratic movement that occurs. Simultaneous pressure must be continued on the ruling regime to develop democratic values and abandon the authoritarian character which has proven increasingly unpopular in this era of globalization